THE PRODUCTIVE-APPRECIATIVE LITERARY LEARNING MODEL: MITIGATING LANGUAGE TEACHERS' MISCONCEPTIONS IN ELEMENTARY SCHOOLS - Dindin Ridwanudin (PD PGMI se Indonesia, 2025)
Literature is an integral component of the Indonesian Language curriculum in elementary schools (SD/MI), playing a strategic role in developing students’ linguistic competence, creativity, and character. However, preliminary field observations and teacher interviews indicate that literary learning is predominantly oriented toward cognitive and theoretical aspects, while affective and productive dimensions remain underemphasized. This condition results in literary instruction that is less meaningful and fails to foster students’ appreciation and creative expression. This study aims to analyze the urgency of positioning literature as a foundation for language learning in elementary education and to propose a Productive–Appreciative Literary Learning Model tailored to students’ developmental characteristics. Employing a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews with elementary school teachers, and document analysis. The findings reveal that literature-based learning effectively integrates language skills and supports character development when implemented through balanced appreciative and productive activities. The proposed model emphasizes dialogic literary appreciation and creative production through prose, poetry, and drama, with adaptive strategies suitable for elementary learners. This model offers a conceptual contribution to strengthening meaningful, student-centered literary learning in primary education.